Born and COVID-19: report of teaching, research and extension project (Research, Society and Development, 2022)
Objective: to report the experience of a research group of two national universities in the development of a teaching, research and extension project aimed at the obstetric population in the context of the COVID-19 pandemic. Methodology: experience report of a project focused on health education and prevention of COVID-19 in the obstetric population. Results: presented and described 32 scientific or technical productions resulting from the project, in the scope of research, extension and teaching, which had as main characteristic the translation of knowledge. Conclusion: the indissociability of teaching, research and extension, allowed advances in academic training and approximation of science with the community. In the pandemic context and, given the vulnerability of the population of pregnant women, puerperiums and neonates, the translation of knowledge through the use of social networks and media, with accessible and illustrated language, proved to be a powerful strategy for the dissemination of evidence to society in general.